Direct bacterial loop-mediated isothermal amplification detection on the pathogenic features of the nosocomial pathogen – Methicillin resistant Staphylococcus aureus strains with respiratory origins. (August 2017) - Lin, Qun; Xu, Pusheng; Li, Jiaowu; Chen, Yin; Feng, Jieyi
Abstract: Loop-mediated isothermal amplification based detection assays using bacterial culture or colony for direct detection of methicillin resistant Staphylococcus aureus (MRSA) had been developed and evaluated, followed by its extensive application on a large scale of clinical MRSA isolated from respiratory origins, including nasal swabs and sputums. Six primers, including outer primers, inner primers and loop primers, were specifically designed for recognizing eight distinct sequences on four targets: 16SrRNA, femA, mecA and orfX. Twenty-seven reference strains were used to develop, evaluate and optimize this assay. Then, a total of 532 clinical MRSA isolates were employed for each detected targets. And the results were determined through both visual observation of the color change by naked eye and electrophoresis. The specific of each primer had been confirmed, and the optimal amplification was obtained under 65 °C for 40 min. The limit of detections (LOD) of bacteria culture LAMP assays were determined to be 10 4 CFU/ml for 16S rRNA, femA, as well as orfX and 10 5 CFU/ml for mecA, respectively. The established novel assays on MRSA detection may provide new strategies for rapid detection of foodborne pathogens. Highlights: Methicillin resistant Staphylococcus aureus strains were the most frequently isolated bacteria in nasal swabs and sputums. This was a novel assay for direct detection of MRSA provided new strategies for rapid detection of foodborne pathogens. The establishment assay not only simplified the operation process but also shorten the detection time.